1987
DOI: 10.1002/bjs.1800741114
|View full text |Cite
|
Sign up to set email alerts
|

Subclavian vascular injuries

Abstract: This study comprises 228 patients with penetrating injuries of the subclavian vessels. The vein alone was involved in 44 per cent, the artery alone in 39 per cent, and both vessels in 17 per cent. The majority of the victims (61 per cent) did not reach the hospital alive, and in those who were operated on the mortality was 15.5 per cent (overall mortality 66 per cent). The overall mortality of venous injuries was significantly higher than the arterial ones (P less than 0.01), probably because of the dangerous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 8 publications
2
30
1
Order By: Relevance
“…Upper extremity neurological deficits are found in slightly more than half of patients, the majority related to brachial plexus injury. 4 Definitive diagnosis is made by angiography because overlying air-filled lungs often preclude ultrasound visualization and the sensitivity of the ABI (ankle brachial index) is affected by collateral blood flow. One retrospective study of 100 patients with periclavicular trauma found that a normal physical exam coupled with a normal chest x-ray eliminated the need for angiography and would not have missed any vascular injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Upper extremity neurological deficits are found in slightly more than half of patients, the majority related to brachial plexus injury. 4 Definitive diagnosis is made by angiography because overlying air-filled lungs often preclude ultrasound visualization and the sensitivity of the ABI (ankle brachial index) is affected by collateral blood flow. One retrospective study of 100 patients with periclavicular trauma found that a normal physical exam coupled with a normal chest x-ray eliminated the need for angiography and would not have missed any vascular injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Busy urban trauma centers report admitting between two and four subclavian vascular injuries per year, although some international trauma centers have reported admitting as high as four patients per month [4,5,15,24]. Subclavian artery injury specifically accounts for 1-2% of all acute vascular injuries [3,4,8,9,26,27]. While the majority of these injuries are penetrating, up to 25% are related to a blunt mechanism of injury [14].…”
Section: Incidencementioning
confidence: 99%
“…The low incidence of subclavian artery injury is primarily explained by the anatomic location and the protective barrier provided by the clavicle and thoracic cage. In a study combining both prospective and retrospective reviews, Demetriades [9] reported that isolated subclavian vein injuries were present in 44% of the patients, isolated subclavian artery involvement in 39%, and combined injuries in approximately 17% of the cases. On the other hand, Lin et al [23] reported that 24 of 54 patients presenting with subclavian artery injuries also sustained associated venous injuries.…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…Penetrating vascular injuries are associated with high mortality rates, with a significant percentage of patients dying before reaching the hospital [1] [2]. Moreover, gunshot vascular injuries may be associated with bone, nerve and muscu-Surgical Science lotendinous damage and treating these complex injuries usually requires a multidisciplinary team approach [3].…”
Section: Introductionmentioning
confidence: 99%